Strategi Pemasaran Layanan Pesantren Salaf-Modern dari Tradisi Menuju Transformasi Digital - Ahmad Dzofron Abiyyu Tsaqib Muhes; Denny Bhekti; Fitdarus Kussuma (Jurnal Pendidikan Tambusai, 2026)
Digital disruption challenges traditional Islamic boarding schools (pesantren salaf-modern) to adapt marketing strategies for millennial parents amid fierce competition. This study aims to analyze the adaptation process of service marketing strategies at Pesantren Darussalam Blokagung, Banyuwangi, focusing on stages, strategies, and impacts on market reach and identity preservation. Employing a qualitative single-case study design, the population comprises managers, staff, parents, and alumni, with a purposive sample of 18 informants (caretaker, communication head, media staff, parents, alumni). Data were collected via semi-structured interviews, participatory observation, and documentation, analyzed using Miles and Huberman's interactive model (data reduction, display, conclusion drawing). Findings reveal a hybrid branding dialectic through three evolutionary phases: replication, interaction, and relational transformation, balancing tradition and digital while facing authenticity paradoxes from commercialization pressures. In conclusion, pesantren must prioritize participatory content curation for sustainable competitiveness without eroding salaf values.